Air pollution from livestock farms, and asthma, allergic rhinitis and COPD among neighbouring residents. Issue 2 (23rd August 2013) - Smit, Lidwien A M; Hooiveld, Mariëtte; van der Sman-de Beer, Femke; Opstal-van Winden, Annemieke W J; Beekhuizen, Johan; Wouters, Inge M; Yzermans, C Joris; Heederik, Dick
Abstract : Objectives: There is an ongoing debate regarding environmental health risks of exposures to dust and microbial agents from livestock farming in the Netherlands. The aims of the study were (1) to investigate associations between indicators of air pollution from livestock farms and asthma, allergic rhinitis and chronic obstructive pulmonary disease (COPD) among neighbouring residents; and (2) to assess associations between farm exposures and endotoxin levels in participants' homes. Methods: Electronic medical records of all 92 548 patients of 27 general practices in a rural area with a high density of animal farms were analysed, followed up by a case-control component using a subsample of the full population. Distance between livestock farms and home address, presence of livestock within 500 m, and particulate matter (PM)10 emissions from farms within 500 m were computed as proxies for farm exposure. Potential confounding was investigated through a case-control questionnaire study in 269 adult patients with asthma and 546 controls. Endotoxin levels were assessed in 493 homes. Results: Modelled PM10 emission was inversely associated with asthma, allergic rhinitis and COPD (p<0.05). A smaller distance to the nearest farm, and the presence of swine, goat and sheep farms were also inversely related to respiratory morbidity, whereas mink farms showed positive associations with asthma and allergic rhinitis. Adjustment for confounding in the case-control study did not change results. Farm exposures were not associated with endotoxin levels in neighbouring residents' homes. Conclusions: In conclusion, indicators of air pollution from livestock farms were inversely associated with respiratory morbidity among neighbouring residents.